An Application of Fuzzy Multiple Linear Regression in Biological Paradigm. (14th September 2022) - Mustafa, Saima; Ghaffar, Shumaila; Bibi, Murrium; Khan, Muhammad Ghaffar; Praveen, Qaisara; Garg, Harish; Saminou, Mahamane
Abstract : The regression model is generally utilized in several fields of study because of its applications. Regression is an extremely incredible approach; it builds up a connection between dependent and independent variables. We have addressed a powerful computational model by utilizing dengue information joined with fuzzy multiple linear regression. Information is accumulated on dengue fever through the survey. This paper is centered on the comparison of the crisp method with fuzzy multiple linear regression, and then, the utilization of a fuzzy multiple regression method is explained after the comparison. We have used multiple regression and then converted the said technique into three fuzzy cases. The effectiveness of the fuzzy multiple regression model is measured by numerical computation and comparison of both techniques. 2020 Mathematics Subject Classification. Primary 30C45; 30C50; 30C80; Secondary 11B65, 47B38.